2011
DOI: 10.1007/s10661-011-2213-5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of hexavalent chromium from contaminated ground water using zero-valent iron nanoparticles

Abstract: Batch experiments were conducted on ground water samples collected from a site contaminated with Cr(VI) to evaluate the redox potential of zero-valent iron (Fe(0)) nanoparticles for remediation of Cr(VI)-contaminated ground water. For this, various samples of contaminated ground water were allowed to react with various loadings of Fe(0) nanoparticles for a reaction period of 60 min. Data showed 100% reduction of Cr(VI) in all the contaminated ground water samples after treatment with 0.20 gL(-1) of Fe(0) nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…The resulting image of nZVI shows that the size of nZVI was approximately 35.57-49.62 nm. It was uniformly aggregated to each other due the strong dipole-dipole magnetic of individual particles [9]. These results strongly confirmed that synthesized nZVI in this study was in nanoscales (<100 nm).…”
Section: Characterization Study Of Nzvisupporting
confidence: 88%
See 4 more Smart Citations
“…The resulting image of nZVI shows that the size of nZVI was approximately 35.57-49.62 nm. It was uniformly aggregated to each other due the strong dipole-dipole magnetic of individual particles [9]. These results strongly confirmed that synthesized nZVI in this study was in nanoscales (<100 nm).…”
Section: Characterization Study Of Nzvisupporting
confidence: 88%
“…The earliest passive in situ treatment introduced is permeable reactive barriers (PRBs) using granular zerovalent iron, however this treatment significant fault is that it can only concentrate on contaminant plumes that flow through the barrier ergo they do not contribute to the active removal of the source [8]. Recent remediation technology which has proven its effectiveness in treating organic and inorganic contaminants is remediation using nanoscale zerovalent iron (nZVI) [8][9][10]. The aforementioned remediation technology is very effective in transforming halogenated organic compounds such as tetrachloroethene (PCE), trichloroethene (TCE), and carbon tetrachloride (CT) into chloride and capable of reducing heavy metals such as lead, uranium, and mercury [8,11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations